Inclusão escolar de crianças autistas: o que acontece quando família e docentes dialogam? - Oliveira, Karoline Mendonça (2021)
This research aims to investigate the experiences of family members and teachers regarding the inclusion process of autistic children in regular schools. To this end, family and teacher were put into dialogue and joint reflection, also intending to analyze the mediation strategies, which could be built collaboratively, in the interactions between these peers, mothers/fathers and teachers. The theoretical framework includes studies that address the concepts of experience, mediation and interaction, based on Vygotsky's historical-cultural psychology (1997, 1998, 2007, 2010), combined with the writings of researchers who study autism, such as Singer (1999 ), Ortega (2008, 2009) and Sinclair (1993) and authors who advocate inclusion in education, such as Mittler (2003), Booth and Ainscow (2011), Lustosa (2002, 2009, 2015), Mantoan (2001, 2003) among others. The methodology used was defined as a qualitative study, of the action research type (BOGDAN; BIKLEN, 1994; MINAYO, 2001). The field research was carried out between the months of August and November 2019. The subjects participating in the research were: 6 (six) fathers/mothers and 1 (one) teacher, as direct collaborators of the investigation. Two meetings were also held, with the participation of only the participating teacher and the mother of one of the children, in order to discuss possible mediation strategies to overcome barriers to school inclusion. In addition to the direct collaborators, we have a group of 4 (four) autistic children (children of the participating families), with whom we performed 4 (four) moments in the space of the FACED/UFC Toy Library. While their parents participated in the research meetings, at the same time, the children were monitored and observed by university student interns. The research identified that the family-school interaction is frequently reported by the participants as conflicting, especially when the members involved in this “family-school/teachers” relationship do not work collaboratively. Some of the barriers to the inclusion of autistic children, presented by the participants, were: prejudice; failures in the mediation of conflicts and absence of actions that build a culture and the development of inclusive educational practices by management and teachers; the distance between family and school; the absence of several accessibility dimensions; overcrowding of classrooms and so on. The complaints that families, in general, are resistant to accepting their children's diagnosis are also highlighted. In turn, families report that teachers are not in favor of school inclusion. The main strategies presented to overcome these obstacles were the continuing education of teachers and the collaboration and interaction between family and school-teachers, advancing in the proposition of collaborative experiences, such as the one we present in this study, an important strategy for building and valuing knowledge that transit in the two segments, family and school. That research and new studies can build, via pedagogical practices, the process of school inclusion of autistic children, contributing to the strengthening of public policies for inclusion and movements for the guarantee of rights in the educational field.